ENVIRONMENTAL MANAGEMENT PERFORMANCE AND GOVERNANCE CHALLENGES IN ROCK MINING OPERATIONS IN BONE BOLANGO REGENCY - Suryadi Syamsuddin; Sukirman Rahim; Marike Mahmud; Fitryane Lihawa (Universitas Medan Area, 2026)
Rock mining plays an important role in supporting regional infrastructure development in Bone Bolango Regency, Gorontalo Province. However, quarry expansion also poses environmental risks that require proper management and supervision. This study evaluates the implementation of environmental management at three active rock mining sites. A mixed-methods approach was applied, integrating field observations, interviews, document analysis, and ambient air quality monitoring to assess compliance with UKL-UPL requirements. The results indicate that environmental management implementation remains inadequate. Major issues include weak erosion and sediment control, limited dust suppression, insufficient waste management, and inconsistent environmental monitoring, despite the availability of formal management documents. Air quality measurements at AF-01, AF-02, and AF-03 show spatial variation in particulate concentrations, influenced by mining intensity and local climatic conditions. Although all values are below national ambient air quality standards, field observations reveal localized dust accumulation, indicating insufficient on-site mitigation. Governance challenges further constrain the application of Good Mining Practices, including limited enforcement capacity, the absence of certified KTT/PJO personnel, and weak inter-institutional coordination. Local communities also reported disturbances related to dust, noise, and truck traffic. Overall, the study emphasizes the need for stronger regulatory oversight, improved technical capacity, and participatory monitoring to support adaptive and sustainable mining management.